Physiological responses to known intake of ergot alkaloids by steers at environmental temperatures within or greater than their thermoneutral zone - Eisemann, Joan H.; Huntington, Gerald B.; Williamson, Megan; Hanna, Michelle; Poore, Matthew (Frontiers in Chemistry, 2014)
Two studies separated effects of dietary ergot alkaloids from effects of feed intake or ambient temperature on respiration rate (RR), heart rate (HR), surface temperature (ST), rectal temperature (RT), blood pressure (BP), serum hormone, and plasma metabolite concentrations in beef steers. The balanced, single reversal design for each experiment used 8 beef steers fed tall fescue seed (2.5 g/kg body weight, (BW)) with (E+) or without (E-) ergot alkaloids as part of a 60:40 switchgrass hay: supplement diet. Periods were 35 d with 21 d of preliminary phase and 14 d of feeding fescue seed once daily. Measures of dependent variables were collected on d 20, 25, 29 and 35 of each period at 0730 (before feeding), 1230 and 1530. In Expt 1 steers weighed 286 kg, gained 0.61 kg BW/d, E+ supplied 2.72 mg ergot alkaloids including 1.60 mg ergovaline per steer daily, and mean minimum and maximum daily ambient temperatures were 23.6 and 32.3°C. In Expt 2 steers weighed 348 kg, gained 1.03 kg BW/d, E+ supplied 3.06 mg ergot alkaloids including 2.00 mg ergovaline daily, and mean minimum and maximum daily ambient temperatures were 11.9 and 17.4°C. Dry matter intake was not affected by fescue seed treatment (P < 0.20) in either experiment. In both experiments, E+ reduced HR (P < 0.01) and increased insulin (P = 0.07). Systolic BP minus diastolic BP decreased (P< 0.05) for E+ in both experiments, due to increased diastolic BP in Expt 1 (P < 0.03) and decreased systolic BP in Expt 2 (P < 0.07). In Expt 1, above the thermoneutral zone, E+ increased (P< 0.05) RR, RT and left side ST in comparison to E-, but in Expt 2, within the thermoneutral zone, E+ and E- did not differ (P < 0.18). Ergot alkaloids from fescue seed affect the cardiovascular system of steers separately from effects of feed intake or environmental temperature. Ergot alkaloids interact with ambient temperatures above the steers’ thermoneutral zone to exacerbate the symptoms of hyperthermic stress.